THE INFLUENCE OF HOST CREDIBILITY, INTERACTIVITY AND LIMITED-TIME OFFER ON PURCHASE DECISION OF FASHION IN TIKTOK LIVE STREAMING SHOPPING - Reynaldo Putra Bhisana; Joy E. Tulung; Regina T. Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The newest trend in the industry of online shopping is live streaming. Live streaming is popular and effective at influencing consumers' decisions to shop online through social media, online marketplaces, and e-commerce, especially in Indonesia. Live-stream shopping is considered by marketers as an effective marketing tactic for business companies to boost sales, reduce costs, and produce unique marketing effects. This study aims to quantitatively show the influence of live streaming shopping on intention made about online purchases. The phenomenon of a new purchasing experience with live streaming shopping is what makes this research urgent. This study will look at how consumer purchase decision for fashion clothing is influenced by host credibility, interactivity, and limited-time offer during live streaming shopping.   Keyword: Host Credibility, Interactivity, Limited-Time Offer, Purchase Decision